Comparison of Midface Advancement by External and Internal Craniofacial Distraction Osteogenesis - Balaji, S. M. (Ann Maxillofac Surg, 2018)
BACKGROUND: Distraction osteogenesis (DO) is employed to address the midface abnormalities using either an external DO (EDO) or an internal DO (IDO) device. There are few studies that have reported EDO and IDO outcomes through cephalometric evaluation. The aim of this retrospective, record-based study is to compare the change in position of the midface resulting from distraction of noncomplicated cases of Le Fort III osteotomies with EDO as well as IDO and compare the groups using standard right facing lateral cephalometry. We hypothesized that there would be no difference between EDO and IDO in terms of displacement (of point of reference) as well as complications. MATERIALS AND METHODS: Retrospective analyses of cases fulfilling inclusion and exclusion criteria were retrieved from archives. Using two sets of right-side cephalometry, preoperative and after consolidation (at the end of the treatment), the changes in Point A and Orbitale (O) as described by Lima et al. were used for the study. Movement in X-axis and Y-axis was noted down and subjected to statistical analysis. Descriptive statistics, the coefficient of variability (expressed as percentage), and the interquartile range (maximum and minimum values) were presented. P ≤ 0.05 was taken as statistically significant. RESULTS: Significant midface advancement was achieved with the procedure. There were five cases of EDO and eight cases of IDO. The age at which patients were operated ranged from 9 to 18 years (mean: 13 years). The mean follow-up time was for 14 ± 8 months. There were eight females (3 – EDO and 5 – IDO) and five males in total. There was no complication in the entire study group. The difference in total bone length gain along the horizontal axis was as follows: 12.19 and 12.84 along the Point A for EDO and IDO and 3.89 and 4.65 along the Point O for EDO and IDO, respectively. The difference was not statistically significant (P = 0.833 and 0.622, respectively). The total movement along the vector at Point A in EDO and IDO was 13.08 and 12.56, respectively, the difference of which was not statistically significant (P = 1); while along the vector at Point O in EDO and IDO, the total movement was 10.98 and 11.48, respectively, the difference of which was not again statistically significant (P = 0.833). DISCUSSION: The significance of the difference in EDO and IDO is discussed using the biomechanical principles and the results deliberated based on the existing literature. CONCLUSION: The positioning of the devices plays a significant role in deciding the outcome. Both the distractors have their distinct advantages and their applications have to be customized.